2017
DOI: 10.1093/cvr/cvw250
|View full text |Cite|
|
Sign up to set email alerts
|

A landscape of circular RNA expression in the human heart

Abstract: Our data provide a detailed circRNA expression landscape in hearts. There is a high-abundance of specific cardiac-expressed circRNA. These findings open up a new avenue for future investigation into this emerging class of RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
245
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(266 citation statements)
references
References 53 publications
18
245
3
Order By: Relevance
“…This is supported by evidence from Boeckel et al who have shown that the circRNA, cZNF292, is regulated by hypoxia in endothelial cells and controls angiogenesis. circRNAs are highly expressed in human heart tissue and are associated with key cardiac genes including Titin (TTN), RYR2 , and DMD (Tan et al, 2017). Further evidence for the role of circRNA in cardiovascular disease is supported by research from Jakobi et al who performed RNA-seq on adult murine hearts and identified a further 575 candidate cardiac circRNAs (Jakobi et al, 2016).…”
Section: Circrnas and Human Diseasementioning
confidence: 99%
“…This is supported by evidence from Boeckel et al who have shown that the circRNA, cZNF292, is regulated by hypoxia in endothelial cells and controls angiogenesis. circRNAs are highly expressed in human heart tissue and are associated with key cardiac genes including Titin (TTN), RYR2 , and DMD (Tan et al, 2017). Further evidence for the role of circRNA in cardiovascular disease is supported by research from Jakobi et al who performed RNA-seq on adult murine hearts and identified a further 575 candidate cardiac circRNAs (Jakobi et al, 2016).…”
Section: Circrnas and Human Diseasementioning
confidence: 99%
“…Due to the advanced sequencing technology and data analysis methods, a growing number of circRNAs have been uncovered from human and murine hearts [84,85,86]. The first circRNA profiling study has identified 575 circRNA species from adult murine hearts and showed that several circRNAs are relevant for the cardiovascular disease pathogenesis [85].…”
Section: Circrnas and Cardiac Remodelingmentioning
confidence: 99%
“…The comparative analyses of the circRNA expression from rats (neonatal and adult), mice (sham or after TAC) and humans (failing, non-failing) have detected more than 9000 candidate circRNAs from each species [86]. Recently, a detailed annotation and analysis of genome-wide circRNA expression uncovered 15,318 cardiac circRNAs in the human heart [84]. All of these provide a good basis for studying the role of circRNAs in heart disease.…”
Section: Circrnas and Cardiac Remodelingmentioning
confidence: 99%
“…11 This study identifies thousands of potential circRNAs that might be involved in cardiomyocyte biology and increases our knowledge on the potential role of this type of ncRNAs in the heart, which has been limited so far to one manuscript from Engelhardt's group. 12 Specifically, the authors analysed ribominus RNAs from human and mouse failing and non-failing hearts, including also data from human embryonic stem cell-derived cardiomyocytes at different stages of differentiation.…”
mentioning
confidence: 99%